Electrochemical oxidation of paraben compounds and the effects of byproducts on neuronal activity - Bosio, M. (2020)
Some organic recalcitrant compounds are not degraded by conventional water treatment systems, making necessary the use of advanced technologies to eliminate these substances. Advanced Oxidation Processes (AOPs) have been extensively proposed to remove emerging contaminants aiming potable water reuse, but literature barely addresses neurotoxic effects of AOPs residual byproducts. These processes involve high costs associated with the electricity, maintenance and oxidizing agent used. However, electrochemical AOPs are techniques based on electron transfer, thus being a clean form of energy and very efficient in the degradation of organic pollutants. Parabens are naturally found in plant sources but most are chemically synthesized, requiring careful treatment to not disturb the environment. In this study, a mixture of parabens (10 mg L−1 each) was degraded by an electrochemical oxidation (EO) system with a Ti/Pt anode. Some parameters, such as the current density (25, 75 and 125 A m−2) and the electrolyte type and concentration (1.5, 3.0 and 5.0 g NaCl L−1 and 3.0 g Na2SO4 L−1) were changed. The best results were obtained with 125 A m−2 and 3.0 g NaCl L−1, which led to the complete degradation of the parabens present in the mixture, after 10 min. In addition to these studies neurotoxicity tests were also performed using the solutions of interest, before and after the EO treatment. It was observed, using the reactive oxygen species (ROS) fluorescent indicator H2DCFDA, that the non-treated solution caused an increase in ROS formation with a signal amplitude of 0.84 ± 0.20 above the baseline. After the EO process the parabens mixture did not lead to a significant ROS change.